Tahlîl Al-tarîqah Al-shâmitah Fî Ta‘lîm Mahârat Al-kalâm - Aulawi, Alfan; Sanah, Siti (Ukazh: Journal of Arabic Studies, 2024)
يتعد مهارة الكلام في تعلم اللغة العربية من أهم المهارات، بحيث يتمكن الطلاب من تحقيق هدف إتقان مهارة الكلام، ومن المحتمل أن تكون الطريقة الصامتة فعالة في مساعدة الطلاب على التواصل باللغة العربية كتفاعل. يهدف هذا البحث إلى تحديد مدى تطبيق أسلوب الطريقة الصامتة في تعليم مهارة الكلام. يستخدم هذا البحث أساليب البحث المكتبي، أما جمع البيانات فيتضمن البحث عن المعلومات وتحليل البيانات واستنتاجها من خلال مراجعة العديد من المجلات والكتب والمقالات والملاحظات المتعلقة بالطريقة الصامتة وأساليب مهارة الكلام. نتائج هذا البحث هي أن تعلم مهارة الكلام يمكن أن يتم باستخدام الطريقة الصامتة، حيث تعتبر هذه الطريقة بديلا في حل صعوبات التحدث التي يواجهها الطلاب. يمكن استخدام طريقة الطريقة الصامتة لتعليم مهارة الكلام من خلال عدة الطرق. بما في ذلك المنهج المادي واختيار المواد التي تناسب الاحتياجات المحلية ومستويات قدرة الطلاب. المدخل التنفيذي، وذلك باستخدام المواد التي تسمح للطلاب بالمشاركة بنشاط في التعليم. المدخل التفاعلي، حيث يقلل من التعليمات الشفهية مع تكلم المعلم إلى الحد الأدنى. المدخل التقويمي، إجراء التقويمات التي لا تركز فقط على النتائج النهائية ولكن أيضًا على عملية التعليم، بما في ذلك مشاركة الطلاب والتقدم الذي يحرزونه Maharah kalam in Arabic language learning is the most important skill, so that students are able to achieve the goal of maharah kalam proficiency, the silent way method has the potential to be effective in helping students communicate Arabic as an interaction. This study aims to determine the application of the silent way method in maharah kalam learning. This study uses a library research method, while data collection is done by searching for information, analyzing and concluding data by reviewing several journals, books, articles and notes related to the silent way and maharah kalam methods. The results of this study are that maharah kalam learning can be done using the silent way method, where this method is an alternative in solving speaking difficulties faced by students. Using the silent way method for maharah kalam learning can be done through several approaches. including the material approach, choosing materials that are appropriate to local needs and student ability levels. The implementation approach, using materials that allow students to actively participate in learning. The interactive approach, minimizing verbal instructions by the teacher speaking as little as possible. The evaluation approach, conducting assessments that not only focus on the final results but also the learning process, including student participation and the progress they make. Maharah kalam dalam pembelajaran bahasa arab merupakan kemahiran yang paling penting, agar siswa mampu mencapai tujuan kemahiran maharah kalam metode silent way berpotensi efektif untuk membantu siswa mengkomunikasian bahasa arab sebagai interaksi. Penelitian ini bertujuan untuk mengetahui penerapan metode silent way dalam pembelajaran maharah kalam. Penelitian ini menggunakan metode penelitian kepustakaan, sedangkan pengumpulan data dengan mencari informasi, menganalisa dan menyimpulkan data dengan menelaah beberapa jurnal, buku, artikel serta catatan terkait dengan metode silent way dan maharah kalam. Adapun hasil penelitian ini adalah pembelajaran maharah kalam dapat dilakukan dengan metode silent way, Dimana metode tersebut merupakan alternatif dalam menyelesaikan kesulitan berbicara yang dihadapi siswa. Menggunakan metode silent way untuk pembelajaran maharah kalam bisa dilakukan melalui beberapa pendekatan. diantaranya pendekatan materi, memilih materi yang sesuai dengan kebutuhan lokal dan Tingkat kemampuan siswa. Pendekatan pelaksanaan, menggunakan materi yang memungkinkan siswa untuk aktif berpartisipasi dalam pembelajaran. Pendekatan interaktif, meminimalkan instruksi verbal dengan cara guru berbicara seminimal mungkin. Pendekatan evaluasi, melakukan penilaian yang tidak hanya berfokus pada hasil akhir tetapi juga proses pembelajaran, termasuk partisispasi siswa dan kemajuan yang mereka buat.